2013
DOI: 10.1007/s12020-013-9985-z
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic T-lymphocyte associated antigen 4 polymorphism and Hashimoto’s thyroiditis susceptibility: a meta-analysis

Abstract: The association between cytotoxic T-lymphocyte associated antigen 4 (CTLA-4) exon-1 +49 A/G polymorphism and Hashimoto's thyroiditis (HT) has been widely studied. The results, however, are mixed. This study provides a comprehensive evaluation of the relationship between the genetic risks of CTLA-4 +49 A/G polymorphism and HT. A meta-analysis was conducted in over 4,600 subjects included in 18 case-control studies that were published up to November 15th, 2012. Our meta-analysis indicated that the CTLA-4 genotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…The G allele has been associated with the reduction of T-cell proliferation (23). A meta-analysis study published in 2014 revealed that the CTLA-4 gene was associated with the risk of HT, and G allele carriers (GG + GA) of this polymorphism, considered as the dominant genetic model, were associated with an increased the risk of HT (24). However, in another meta-analysis study, this association was not identified (25).…”
Section: Discussionmentioning
confidence: 99%
“…The G allele has been associated with the reduction of T-cell proliferation (23). A meta-analysis study published in 2014 revealed that the CTLA-4 gene was associated with the risk of HT, and G allele carriers (GG + GA) of this polymorphism, considered as the dominant genetic model, were associated with an increased the risk of HT (24). However, in another meta-analysis study, this association was not identified (25).…”
Section: Discussionmentioning
confidence: 99%
“…These two polymorphisms are associated with thyroid antibody production [ 27 , 28 ], GD relapse [ 25 ], Graves ophthalmopathy [ 29 , 30 ], and susceptibility to GD [ 23 , 31 ] and HD [ 32 , 33 ]. Recently, many meta-analyses have also demonstrated the association between CTLA4 polymorphisms and AITD [ 34 38 ]. However, studies on GD in pediatric populations are limited and inconsistent [ 39 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, several immunological alterations have been found in these patients, such as HLA-DR antigen expression in thyrocytes, the presence of growth-stimulating immunoglobulins, and an increase in dendritic cells and lymphocytes, which suggest the possibility of autoimmune problems (1,(8)(9)(10). Although many of these findings may be an epiphenomenon of other primary defects in immunoregulation, the alteration of lymphocyte populations indicates a primary defect (6,7,10,(12)(13)(14)(15)(16)(17)(18). Variations in several genes have been studied as possible risk factors for Hashimoto thyroiditis.…”
Section: Introductionmentioning
confidence: 99%
“…Other genes that have been associated with AIT help regulate the immune system or are involved in normal thyroid function. Most of the genetic variations that have been discovered are thought to have a small impact on a person's overall risk of developing this condition (14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation